The mediating effect of public opinion on public policy : exploring the realm of health care - Chard, Richard E., 1965- (SUNY series in public policy., 2004)
"Using health care policy to develop a theory of how public opinion influences public policy outcomes, Richard E. Chard draws on data ranging from presidential approval ratings to polls conducted during the debate over the Health Security Act. Over the last five decades the relationship has been a complex one, yet there are clear indications that health care policy development has been controlled to a great extent by public opinion. Chard argues that policy change is either static or dynamic because public opinion, the underlying force, is itself dynamic at times and static at others, and concludes that this model of change is applicable to all policy areas, not just health care."--Jacket